A Multilevel Investigation of Factors Influencing Employee Service Performance and Customer Outcomes - Liao, Hui; Chuang, Aichia (Academy of Management Journal, 2004)
Previous work on service performance has focused on either organization- or individual-level analysis. This multilevel study of 257 employees, 44 managers, and 1,993 customers from 25 restaurants demonstrated that both individual- and store-level factors were significantly associated with employee service performance: conscientiousness and extraversion explained within-store variance, and service climate and employee involvement explained between-store variance. Further, employee service performance aggregated to the store level explained between-store variance in customer satisfaction and loyalty.